Three Examples of Engagement through Photovoice - Etmanski, Catherine; Kyte, Alison; Cassidy, Michelle; Bade, Nikki (Engaged Scholar Journal, 2022)
Addressing the complex challenges of today’s world requires our collective creative capacity. As such, arts-based methods which promote creativity are increasingly important means of engaging people in the issues that matter most to them. This article focuses on one arts-based method, Photovoice, which is a “process by which people can identify, represent, and enhance their community through a specific photographic technique” (Wang & Burris, 1997, p. 369) where participants take photos in response to a question or topic of inquiry. To explore this engagement method, we draw from the methodological insights gleaned from three Master’s Arts in Leadership capstone projects that employed Photovoice (or variations thereof) as one method of inquiry.The article is organized as follows: We begin by reviewing Photovoice as a research and engagement method and then summarize the three projects, which occurred in two nonprofit organizations and one public sector institution. In the discussion, we then compare and contrast the methodological insights emerging from these projects, including the extent to which each project: (a) enabled workers at various levels of organizational hierarchies to share their voices; (b) required careful attention to ethics; and (c) generated relationships among participants. As this is a methodological paper, our emphasis here is to highlight the process and impact of using Photovoice as a method rather than sharing each of the study findings and conclusions. In each example, Photovoice as both a research and engagement method enabled participants to play a leadership role in participatory engagement, thus deemphasizing top-down decision-making and promoting more integrated approaches to research and leadership as engagement.